2020
DOI: 10.1128/iai.00316-20
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Ehrlichia chaffeensis Genes Critical for Its Persistent Infection in a Vertebrate Host Are Identified by Random Mutagenesis Coupled with In Vivo Infection Assessment

Abstract: Ehrlichia chaffeensis, a tick-transmitted obligate intracellular rickettsial agent, causes human monocytic ehrlichiosis. In recent studies, we described substantial advances in developing random and targeted gene disruption methods to investigate the functions of E. chaffeensis genes. We reported earlier that the Himar1 transposon-based random mutagenesis is a valuable tool in defining E. chaffeensis genes critical for its persistent growth in vivo in reservoir and incidental hosts. The method also aided in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 79 publications
0
27
1
Order By: Relevance
“…7 c, Table S 4 ). Previous studies have indicated that E. chaffeensis TRP proteins are highly immunogenic in infected patients and animals [ 144 ], and could play important roles in host–pathogen interactions [ 143 , 145 152 ]. Our recent study using Himar1 transposon mutagenesis of Ehrlichia sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 c, Table S 4 ). Previous studies have indicated that E. chaffeensis TRP proteins are highly immunogenic in infected patients and animals [ 144 ], and could play important roles in host–pathogen interactions [ 143 , 145 152 ]. Our recent study using Himar1 transposon mutagenesis of Ehrlichia sp.…”
Section: Resultsmentioning
confidence: 99%
“…During the review process of the present paper, Wang et al . [ 152 ] reported (published online on August 3, 2020) that an Himar1 transposon insertion mutant in TRP120 gene of E. chaffeensis was recovered in DH82 cells. This mutant had an initial lag phase but recovered afterwards in DH82 cell culture; however, it could not infect dogs when mixtures of E. chaffeensis transposon mutants were inoculated into dogs.…”
Section: Notesmentioning
confidence: 99%
“…3C ), although the mutant tested positive for the remaining six genes (data not shown). We recently generated another mutant with functional disruption in ECH_0665, the last gene of the gene cluster ( 39 ). Unlike the ECH_0660 mutation, this mutation has no impact on the pathogen’s in vivo growth, as it progressed very similarly to that of the wild type when assessed in a vertebrate host ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, transcript levels were similar to wild-type or slightly downregulated for the ECH_0665 mutant. We recently reported that this mutant has a minimal impact on its in vivo growth (39).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation